2020
DOI: 10.1371/journal.pone.0228740
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of RP-1 peptide conjugate with ferrocene group

Abstract: Parasitic diseases are a neglected and serious problem, especially in underdeveloped countries. Among the major parasitic diseases, Leishmaniasis figures as an urgent challenge due to its high incidence and severity. At the same time, the indiscriminate use of antibiotics by the population is increasing together with resistance to medicines. To address this problem, new antibiotic-like molecules that directly kill or inhibit the growth of microorganisms are necessary, where antimicrobial peptides (AMPs) can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 92 publications
2
17
0
Order By: Relevance
“…Co-conjugation with Fc molecules in the bi-functional MNP conjugate affected the extent of IgG coverage, resulting in a lower number of IgG molecules per magnetic particle. In addition, it has been suggested that ferrocenium radicals may inhibit the growth of E. coli due to oxidative damage to the cell wall [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-conjugation with Fc molecules in the bi-functional MNP conjugate affected the extent of IgG coverage, resulting in a lower number of IgG molecules per magnetic particle. In addition, it has been suggested that ferrocenium radicals may inhibit the growth of E. coli due to oxidative damage to the cell wall [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the ways to circumvent the situation triggered by bacterial resistance is to invest in research and development focusing on new molecules with antibacterial potential, among which antimicrobial peptides (AMPs) stand out. These molecules are constituents of the defense systems of several organisms, are widely distributed in nature, and act against various pathogens, including bacteria, fungi, Leishmania , and viruses [ 3 , 4 ]. AMPs are promising novel antibiotics that kill multidrug-resistant bacteria and show activity against some bacteria that are considered a priority by the WHO [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bio-organometallic pendant ferrocenyl (Fc) peptide conjugates have been explored extensively . This class of peptides has allowed researchers to design systems with new redox triggered functions, such as chirality organization [1,11], chirality dependence charge transfer rate [2], photodynamic anticancer [3,7], antibacterial [4,10], antimicrobial [6] and antimalarial [7] activities, supramolecular gelation [8,18], potential bioinspired electronic materials [9], changes in the self-assembly [12], sensory applications [13,14,19], enzymatic fuel cells [15,16] and bioelectrocatalysts [22]. In particular, we have employed a single Fc group as a scaffold to support peptide secondary structural motifs, such as 3 10 -helices with α-amino isobutyric acid (Aib) [23] or L -2,3-diamino propionic ( L -Dap) acid [24], and the 2.0 5 -helix based on C α,β -didehydroalanine (∆Ala) [25].…”
Section: Introductionmentioning
confidence: 99%